Optimization Of Glucose and Nitrogen Consentration In Medium Nata de Citrus From Calamansi Orange Juice - Anggreani, Nita; Jais, Ahmad; Murcitro, Bambang Gonggo; Maulidia, Anggun; Dia Safitri, Egi (Department of Technology of Agricultural product (THP) Jambi University, 2020)
Calamansi orange is a superior fruit that is being promoted for planting in Bengkulu Province. Calamansi citrus preparations have only a few variations, generally made into calamansi orange syrup. This research was conducted to make a new processed variation from calamansi orange juice to Nata de Citrus products and to optimize the nata fermentation medium based on glucose and nitrogen concentrations. This study used a factorial completely randomized design (CRD) with 2 factors. The first factor is the variation of glucose in the medium by diluting orange juice 0 times ( no diluting); 0.5 times; 1 times; 1.5 times and 2 times. The second factor is the variation of nitrogen in the medium obtained by adding 0.6% Ammonium Sulfate; 0.7% and 0.8%. The results were analyzed using ANOVA and for significantly different variables, further analyzed using orthogonal polynomial order 2. The optimum results were obtained at a glucose concentration of 1.76% (dilution of calamansi orange juice 1.65 times) and a nitrogen concentration of 0.17% (ammonium sulfate 0.8%).